A simple and benign protocol for the synthesis of a deep eutectic solvent-based hydrophilic molecularly imprinted resin in water for excellent selective molecular recognition in aqueous phase. Issue 14 (30th June 2021) - Wang, Mingwei; Qiao, Fengxia; Yan, Hongyuan
Abstract : A new deep eutectic solvent-based hydrophilic molecularly imprinted resin with excellent molecular recognition in aqueous phase was developed for the first time via a simple, efficient and green protocol. Abstract : Molecularly imprinted polymers (MIPs) are conventionally synthesized in organic solvents, resulting in poor compatibility with water and weak molecular recognition of targets in aqueous environments; hence, developing a green process to synthesize such MIPs would make the procedure more sustainable and the production more environmentally scalable. To achieve these objectives, a new deep eutectic solvent-based hydrophilic molecularly imprinted resin (DES-HMIR) was synthesized in water with excellent selective molecular recognition in aqueous phase; thus, the process pre-empts the consumption of large amounts of organic solvents. During the synthesis, the DES was simultaneously used as a porogen and cosolvent for the template, in order to improve the imprinting factor and increase the specific surface area of the DES-HMIR. Owing to its specific recognition performance and water phase compatibility, the DES-HMIR can specifically recognize and extract targets from aqueous matrices. The obtained DES-HMIR showed excellent specificity towards analytes compared to commercial adsorbents such as HLB, C18, silica and SCX. The DES-HMIR could be easily regenerated with only 0.1 mL of 50% acetonitrile–water at room temperature and reused 26 times without a significant decrease in the adsorption capacity at pH 7. The DES-HMIR demonstrated excellent and specific recognition properties toward its target molecules in aqueous matrices, thereby allowing its use in a variety of promising applications, including environmental, biological, and clinical applications. Finally, the synthesis strategy proposed in this work provides a simple, efficient and green protocol for the preparation of water-compatible MIPs.